Biomass torrefaction: An overview on process parameters, economic and environmental aspects and recent advancements. (April 2020) - Cahyanti, Margareta Novian; Doddapaneni, Tharaka Rama Krishna C.; Kikas, Timo
Highlights: Torrefaction improves biomass properties to a level comparable with coal. Environmental and economic aspects of torrefaction are discussed. Improving quality and cost competitiveness of torrefaction products is essential. Abstract: Torrefaction is one of the pretreatment processes used to overcome the disadvantages of using biomass as a fuel such as low energy density, high moisture, and oxygen contents. The torrefaction increases energy density, hydrophobicity, and reduces grinding energy requirement of biomass. This paper provides a review of the recent advancements in the torrefaction process. The discussion will cover the environmental and economic aspects of the torrefaction process and torrefied pellets, and various applications of torrefaction products. The cost competitiveness of torrefied pellets is one of the major concern of the torrefaction process. Integrating the torrefaction with other processes makes it economically more viable than as a standalone process.